A saúde do(a) trabalhador(a) da educação superior em Serviço Social em tempos de ofensiva neoliberal - Barbosa, Selma de Melo (2021)
This research has as object of study the societal transformations in the last decades, and still in course, emphasizing its implications in the working relations and illness of the education workers in higher education. In this way, we aim to analyse how the neoliberal offensive of the State changes the working relations in higher education and how this change establishes a sickening working process. To achieve this general objective, we list four specific objectives: Identify changes in the Health Care and Workplace Safety Policy of the Federal Public Servant (PASS) after the State Reform in 1998; Analyse how the changes in the working environment and the reform of the State impacted the health of workers in higher education institutions; Analyse the conceptual and methodological differences between the field of Worker Health and Occupational Health. For this, we use the Sucupira Platform as a database and refine our search using the Social Service as area of knowledge and, as a scope, theses, and dissertations. After this first survey, we analysed the studies realized by the Social Service area whose research subjects were education workers. The bibliographic review was carried out in order to understand the historical context that precedes the implementation of SIASS and to map and analyse researches that have as scope the changes in the working relationships brought about by the public management in the context of the health of this worker